Role of C-Peptide in the Regulation of Microvascular Blood Flow. (28th July 2008) - Forst, T.; Kunt, T.; Wilhelm, B.; Weber, M. M.; Pfützner, A.
Abstract : During the recent years, the role of C-peptide, released from the pancreatic beta cell, in regulating microvascular blood flow, has received increasing attention. In type 1 diabetic patients, intravenous application of C-peptide in physiological concentrations was shown to increase microvascular blood flow, and to improve microvascular endothelial function and the endothelial release of NO. C-peptide was shown to impact microvascular blood flow by several interactive pathways, like stimulatingNa + K + ATPase or the endothelial release of NO. There is increasing evidence, that in patients with declining beta cell function, the lack of C-peptide secretion might play a putative role in the development of microvascular blood flow abnormalities, which go beyond the effects of declining insulin secretion or increased blood glucose levels.